Genetically Modified Fauna and Flora in the Hunger Games by Suzanne Collins - Zielonka, Beata (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The purpose of this article was to demonstrate and inspire the fantasy literature addressed to young readers with motifs of flora and fauna. Plants and animals used by Capitol were subjected to intimidation, and were eventually used against the creator. Well-developed technology has created a world of chimeras and hybrids. Genetic animals are examples of dehumanization tributes and represent the final debasement districts. They hurt people physically and mentally, without any inhibitions. The names of the characters refer to the flora. Berries are a symbol of rebellion and social revolution and the nuns hope. Paradoxically, positively indexed in culture became the rose flower of death and hypocrisy of President Snow.